Astrócitos são resistentes à infecção in vitro pelo vírus da encefalite de Saint Louis: estudo da citotoxicidade e astrogliose - Zuza, Adriano Lara (2015)
Saint Louis Encephalitis Virus (SLEV) is a flavivirus that infects humans through Culex mosquito bite. It causes Saint Louis Encephalitis (SLE), a disease that affects mainly the elderly with a mortality rate of 17% and various severity clinical presentations. In order to reach the central nervous system (CNS) from circulating blood the pathogen must cross a barrier formed by endothelial cells and astrocytes, the blood-brain-barrier (BBB). Astrocytes are the most common glial cell type in CNS, their role is to keep neural tissue homeostasis, control neuroinflamation and immune response. Althought astrocytes can be infected by flavivirus, there are few studies to evaluate its infection and cell alterations post SLEV exposure. For astrocyte plays an essential role in CNS functioning, they were investigated for morphologic alterations and activation (astrogliosis), immunological response via MHC-I and apoptosis induction via caspase-3 activation post-infection. A comparative study using plaque forming units (PFU) and MTT salt assay was performed to determine viral titer revealing that both methods can be used to access viral titres of a sample with similar results. VERO cells shown higher cytotoxicity and mortality rates than astrocytes when infected with SLEV. Besides, flaviviral exposure unleashed astrocyte immune response marked by raise in MHC-I expression and astrogliosis, characterized by intense GFAP expression, and increase in number and length of cytoplasmic processes. When exposed to growing viral concentrations, it has been observed a proportional increase of caspase-3 expression, also showing nuclear envelope destruction. Immune staining with anti-SLEV antibody revealed that the virus displayed a perinuclear location during the replication process. The great SLEV resistance of astrocytes suggests that other infection mechanisms, as BBB breakdown must be associated in the neuroinvasive form of SLEV infection. Also astrocyte might play a role in chronic infection of CNS.